Determinant Audit Delay In Indonesia Islamic Banks - Aulia Rahman Harahap; Saparuddin Siregar; Nurlaila Nurlaila (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2022)
This study was designed to test the factors influencing audit delay at the Indonesia Islamic Bank. This type of research is a qualitative type of research with an observation period of 2015 to 2020. The variables tested for their effect on audit delay are the number of audit committee meetings, the size of the internal audit and Entity complexity.   This study used a statistical tool, namely eviews 12. The research findings are as follows: the number of audit committee meetings has a positive influence on audit delay but is not significant, and the size of the internal audit has a significant positive influence audit delay and Entity complexity audits have a significant negative effect on audit delay.